IMPLEMENTASI COMMUNITY BASED EDUCATION DALAM PENGEMBANGAN PENDIDIKAN PESANTREN DI WONOGIRI - Purwanti, Eka Yuni (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2023)
Community Based Education is education that is organized based on social characteristics, religion, culture, community potential, and community aspirations as the embodiment of education from, by, and for the community. Islamic boarding schools as the embodiment of community based education. This research is a qualitative case study that takes 3 locations to provide a complete picture of the concept, strategy, and SWOT analysis. Research objects at Gani Tirtoasri Islamic Boarding School, Sunan Gunung Jati Islamic Boarding School and Al Ibanah Islamic Boarding School. The concept that exists in pesantren can be seen in its management which includes planning, organizing, actuating, and controlling. While the strategy used is the marketing mix strategy. And for SWOT analysis there are several strengths, weaknesses, opportunities and threats as a basis for the development of education in Islamic boarding schools